Effects of Transcranial Direct-Current Stimulation and Cognitive Training on Individuals with Mild Cognitive Impairment and Dementia: A Systematic Review and Meta-Analysis - Ka Yin Chu; King Hei King Cheng (Journal of Modern Rehabilitation)
Introduction: We aimed to systematically evaluate the most recent evidence regarding the potential short-term and long-term synergistic effects of transcranial direct-current stimulation (tDCS) and cognitive training (CT) on the memory of individuals with mild cognitive impairment (MCI) or dementia and to explore the optimal treatment protocol. Materials and Methods: Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, a comprehensive literature search on PubMed, Medline, CINAHL and EMBASE was conducted to identify eligible randomized controlled trials (RCTs) published up to December 2022. The identified studies were summarized and analyzed to examine the efficacy of the combined intervention. Results: Ten studies involving participants with MCI or dementia were included. Four RCTs with memory-related outcomes were analyzed. A small-to-medium effect size (ES) of 0.28 was found for the short-term effect (95% CI, 0.02%, 0.55%). However, the long-term effect was non-significant, with an ES of 0.17 (95% CI, -0.09%, 0.44%). Conclusion: The combined intervention appears to effectively mitigate cognitive decline in the short term only. Optimal treatment protocol remains inconclusive due to heterogeneity among studies. More robust evidence is required to determine whether the combined approach can serve as an effective intervention in clinical practice.